2021
DOI: 10.3389/fimmu.2021.690467
|View full text |Cite
|
Sign up to set email alerts
|

Immunomonitoring of Stage IV Relapsed Neuroblastoma Patients Undergoing Haploidentical Hematopoietic Stem Cell Transplantation and Subsequent GD2 (ch14.18/CHO) Antibody Treatment

Abstract: Haploidentical stem cell transplantation (haplo SCT) in Stage IV neuroblastoma relapsed patients has been proven efficacious, while immunotherapy utilizing the anti-GD2 antibody dinutuximab beta has become a standard treatment for neuroblastoma. The combinatorial therapy of haplo SCT and dinutuximab may potentiate the efficacy of the immunotherapy. To gain further understanding of the synergistic effects, functional immunomonitoring was assessed during the clinical trial CH14.18 1021 Antibody and IL2 After hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In addition, dinutuximab beta markedly improved NK-cell cytokine secretion, degranulation, and cytotoxicity. Collectively, the combination of haplo HSCT and dinutuximab beta for the treatment of stage IV relapsed neuroblastoma was feasible ( Seitz et al, 2021 ). Cheung et al reported that in a phase 2 clinical trial ( ClinicalTrials.gov NCT00911560) one hundred two patients with HR-NB and a history of Parkinson’s disease (PD) received treatment with the GD2/GD3 vaccine plus β-glucan.…”
Section: Gangliosidesmentioning
confidence: 99%
“…In addition, dinutuximab beta markedly improved NK-cell cytokine secretion, degranulation, and cytotoxicity. Collectively, the combination of haplo HSCT and dinutuximab beta for the treatment of stage IV relapsed neuroblastoma was feasible ( Seitz et al, 2021 ). Cheung et al reported that in a phase 2 clinical trial ( ClinicalTrials.gov NCT00911560) one hundred two patients with HR-NB and a history of Parkinson’s disease (PD) received treatment with the GD2/GD3 vaccine plus β-glucan.…”
Section: Gangliosidesmentioning
confidence: 99%
“…OS at 2 and 3 years was 68.6% and 58%, respectively, and EFS at 2 and 3 years was 51.2% and 46.9%, respectively (median follow-up 2.5 years) [21]. Thus, the combinatorial therapy of haplo-SCT and dinutuximab beta seem to increase the efficacy of immunotherapy [22].…”
Section: Dinutuximab Beta Clinical Trial Programmentioning
confidence: 99%
“…Having demonstrated the safety of haplo-HSCT, this technique has been combined with the infusion of chimeric anti-GD2 mAbs and IL-2 in children with relapsed HR-NB [ 86 ]. The immune monitoring of this cohort of patients provided some very relevant information.…”
Section: Haploidentical Hematopoietic Cell Transplantation In Hr-nb P...mentioning
confidence: 99%